KUALITAS LAYANAN INTERNAL YANG MEMENGARUHI KEPUASAN NASABAH DENGAN MENGGUNAKAN KUALITAS LAYANAN EKSTERNAL SEBAGAI VARIABEL MEDIASI - Evi Susanti (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2018)
This study develops the role of service quality both internal and external service quality to improve customer satisfaction at shariah banking service office in DKI Jakarta province. This study discusses the study on two areas of science namely Human Resource Management and marketing management science. The target in this study was 121 shariah banking service offices. Sample is selected using purposive sampling. The liniear Structural Equation Modelling (SEM) was adopted to verfy the model. The results are (1) internal service quality has a positive significant and direct influence on external service quality (2) external service quality has a positive significant and direct influence on customer satisfaction (3) internal service quality has significantly positive influence on external service quality, which in turn affects the customer satisfaction in a significant and positive manner. In summary, the external service quality has a partially mediating effect.